(untitled) (Physical Education, Health and Social Sciences, 2026)
Pak Choi (Brassica rapa L. var. chinensis), a highly nutritious green vegetable, is well-known for its soft leaves and rich vitamins, minerals. While commonly grown in Asia, Europe, and North America, its adaptation to cold winter temperatures in Peshawar, Pakistan, is now largely unknown. The purpose of this study was to evaluate Pak Choi’s agro-morphological features, growth habits, vegetation placement, and productivity potential during the winter season of 2022-2023 at the University of Agriculture in Peshawar. Morphological aspects such as plant height, girth, root length, and leaf length and dimensions were measured, as well as yield aspects such edible green weight, root weight, total biological weight, and leaf number were recorded. The results revealed that Pak Choi is very adaptive to local winter environments, with a highest plant height of 33.97 cm, girth of 31.5 cm, leaf length of 21.1 cm, and leaf width of 12.3 cm. The vegetative weight of each plant averaged between 291 and 322.3 g, with edible green biomass comprising for 155 and 169.7 g. The predicted production per hectare ranged from 26.3 to 30.7 tons, demonstrating high productivity potential. The results obtained indicate that Pak Choi may be effectively incorporated into Peshawar’s winter growing practices, delivering nutritional and economic advantages to farmers while also serving as a foundation for further study and crop enhancement projects.